HUBUNGAN LUAS DAUN TERHADAP PERTAMBAHAN BERAT KERING RUMPUT GAJAH DI BERBAGAI PERLAKUAN DI MEDIA TAILING TIMAH - Nyayu Siti Khodijah; Rujito Agus Suwignyo; M. Umar Harun (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2018)
Elephant grass (Pannisetum purpureum) can grow in various types of land conditions and produces and is resistant to environmental stress. The predominant sand tin tailing conditions and poor nutrients cause limited plant growth above them. This research tested some kind of fertilizer treatment on sand tailing media after tin addition by using elephant grass plants. The results showed that the type of fertilizer had significant effect on the specific leaf area variant, the ratio of leaf area and the leaf weight ratio. Overall growth were greatly depressed on the 100% tailings treatment. Lime applied in conjunction with NPK fertilizer was not show the total leaf weight that was different from the addition of NPK alone. NPK fertilizers better influence the growth of elephant leaves in tin tailings than organic fertilizers. The best treatment was obtained on organic fertilization with NPK inorganic fertilization. The association of total dry weight of elephant grass with specific area of elephant grass leaf was only visible in organic fertilization treatment together with NPK inorganic fertilizer. In the best condition of elephant grass growth, the specific leaf area had a significant role to increase the total weight of the plant with the value of r2 = 0.864 or LDS will affect the total dry weight of elephant grass in the tailings medium with the addition of organic and inorganic materials NPK of 86.4 percent the remaining 13.6% increase in total dry weight was influenced by factors other than specific leaf area.